"Bebida helada de jengibre (Zingiber officinale) con niveles de miel de abeja" - Mendoza Luna, Suannie Vanessa (2020)
The consumption of surgary drinks in the market contitutes a benchmark for the type of life that people lead, the ease and lack of time make these drinks are consumed daily by entire families and school children, since times ago honey and ginger are renowned for their antioxidant, and antibacterial properties. The research consisted of the combination of the two aforementioned products, with different percentages of bee honey (5 -7.5 - 10 - 12.5 -15%). once the drink was made, the physicochemical, microbiogical and organoleptic characteristic were analyzed, in addition determining the benefit/cos ratio. Thr samples were analyzed in the bromatology laboratory of the State Tecnical University of Quevedo................................................................